CpG methylation changes associated with hyperglycemia in type 1 diabetes occur at angiogenic glomerular and retinal gene loci - Xiaojian Shao; Sophie Le Fur; Warren Cheung; Marie-Pierre Belot; Kevin Perge; Natacha Bouhours-Nouet; Candace Bensignor; Lucie Levaillant; Bing Ge; Tony Kwan; Mark Lathrop; Tomi Pastinen; et al. (Scientific Reports)
Abstract Chronic hyperglycemia is a major risk factor for glomerular or retinal microangiopathy and cardiovascular complications of type 1 diabetes (T1D). At the interface of genetics and environment, dynamic epigenetic changes associated with hyperglycemia may unravel some of the mechanisms contributing to these T1D complications. In this study, blood samples were collected from 112 young patients at T1D diagnosis and 3 years later in average. Whole genome-wide bisulfite sequencing was used to measure blood DNA methylation changes of about 28 million CpGs at single base resolution over this time. Chronic hyperglycemia was estimated every 3–4 months by HbA1c measurement. Linear regressions with adjustment to age, sex, treatment duration, blood proportions and batch effects were employed to characterize the relationships between the dynamic changes of DNA methylation and average HbA1c levels. We identified that longitudinal DNA methylation changes at 815 CpGs (with suggestive p-value threshold of 1e-4) were associated with average HbA1c. Most of them (> 98%) were located outside of the promoter regions and were enriched in CpG island shores and multiple immune cell type specific accessible chromatin regions. Among the 36 more strongly associated loci (p-value < 5e-6), 16 were harbouring genes or non-coding sequences involved in angiogenesis regulation, glomerular and retinal vascularization or development, or coronary disease. Our findings support the identification of new genomic sites where CpG methylation associated with hyperglycemia may contribute to long-term complications of T1D, shedding light on potential mechanisms for further exploration.